2016
DOI: 10.1093/mnras/stw2589
|View full text |Cite
|
Sign up to set email alerts
|

A unifying evolutionary framework for infrared-selected obscured and unobscured quasar host haloes

Abstract: Recent measurements of the dark matter halo masses of infrared-selected obscured quasars are in tension -some indicate that obscured quasars have higher halo mass compared to their unobscured counterparts, while others find no difference. The former result is inconsistent with the simplest models of quasar unification that rely solely on viewing angle, while the latter may support such models. Here, using empirical relationships between dark matter halo and supermassive black hole masses, we provide a simple e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 107 publications
(146 reference statements)
1
20
0
Order By: Relevance
“…Recent works support the idea that the host galaxy has enough dust (Burtscher et al 2016) to cause obscuration of the broad-line region. DiPompeo et al (2017) estimate the fraction of IR-selected "obscured" AGNs that are obscured by dust outside the torus to be ∼25%, while Buchner & Bauer (2017) estimate that 40% of all AGNs have considerable host galaxy obscuration. But objects with large measured column densities > N 10 H 23.5 cm −2 cannot be explained by host galaxy obscuration and need heavy obscuration around the nucleus.…”
Section: Physical Implications Of Agn Obscurationmentioning
confidence: 99%
“…Recent works support the idea that the host galaxy has enough dust (Burtscher et al 2016) to cause obscuration of the broad-line region. DiPompeo et al (2017) estimate the fraction of IR-selected "obscured" AGNs that are obscured by dust outside the torus to be ∼25%, while Buchner & Bauer (2017) estimate that 40% of all AGNs have considerable host galaxy obscuration. But objects with large measured column densities > N 10 H 23.5 cm −2 cannot be explained by host galaxy obscuration and need heavy obscuration around the nucleus.…”
Section: Physical Implications Of Agn Obscurationmentioning
confidence: 99%
“…Qualitatively, treating the effective obscuring covering fraction as a function of time in a quasar's evolution provides a simple explanation for the fact that obscured and unobscured quasars have different observed properties such as host dark matter halo mass. DiPompeo et al (2017b) quantitatively showed that this evolutionary sequence is able to recreate clustering measurements. The key piece to evolutionary models is understanding the timescales at which the host galaxy and the quasar/black hole evolve.…”
Section: Implications For Evolutionmentioning
confidence: 94%
“…One commonly invoked picture of quasar evolution is that quasar activity is triggered by a dramatic event such as a merger or disk instability. The quasar then remains active in an obscured state until it rids itself of obscuring material via radiative and mechanical feedback to become unobscured (e.g., Sanders et al 1988;Di Matteo et al 2005;Hopkins et al 2008;Alexander & Hickox 2012;DiPompeo et al 2017b;Hickox & Alexander 2018). Qualitatively, treating the effective obscuring covering fraction as a function of time in a quasar's evolution provides a simple explanation for the fact that obscured and unobscured quasars have different observed properties such as host dark matter halo mass.…”
Section: Implications For Evolutionmentioning
confidence: 99%
See 2 more Smart Citations